Da Pola a Ravenna: l’opera del vescovo Massimiano tra politica, religione e arte (VI secolo) - Rizzardi, Clementina (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
Born in Pola, Deacon of the local Church, consecrated Bishop in Patras of Acaia by Pope Virgil (on 14 October 546) by order of Justinian and sent by him to Ravenna, Maximian was the first to rank as Archiepiscopus. Represented and portrayed close to the Emperor, in the famous mosaic panel of Saint Vitale in Ravenna, he became one of the most powerful levers and influential men in the imperial politics of the Western world. This was made possible thanks to the artistic as well as legislative activities. Another reason is the restoration of orthodoxy, which had been strongly undermined by the highly dominant Arian religion during the reign of the Goths. Perfectly adapting himself to the concept of art as “instrumentum regni” promoted by Justinian, in Ravenna he founded or consecrated and restored many churches; others were built in his native Istria. He was the most influential leader of that artistic and cultural Koinè of the whole Adriatic area, expertly surveyed and investigated by Nikola Jakšić’s studies and research.